2006
DOI: 10.1001/jama.295.24.2851
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy vs Zopiclone for Treatment of Chronic Primary Insomnia in Older Adults

Abstract: clinicaltrials.gov Identifier: NCT00295386.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
295
0
17

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 524 publications
(325 citation statements)
references
References 42 publications
13
295
0
17
Order By: Relevance
“…In one of these studies, CBT showed better results than zopiclone; 25 in the other study, flurazepam was superior to progressive muscle relaxation plus cognitive distraction (PMR/ CD), sleep restriction and stimulus control (SR/SC) or sleep hygiene education. 28 Most of the studies compared mind-body intervention with no treatment (waiting-list control).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In one of these studies, CBT showed better results than zopiclone; 25 in the other study, flurazepam was superior to progressive muscle relaxation plus cognitive distraction (PMR/ CD), sleep restriction and stimulus control (SR/SC) or sleep hygiene education. 28 Most of the studies compared mind-body intervention with no treatment (waiting-list control).…”
Section: Resultsmentioning
confidence: 98%
“…In the same study, the CBT group exhibited an increase in sleep stages 3 and 4 and a decrease in time awake during the PSG as compared to the zopiclone or placebo groups. 25 In another study, cognitive changes were correlated with improvements noted on both objective (PSG) and subjective measures of insomnia symptoms, particularly within the CBT group. 31 …”
Section: Polysomnography (Psg)mentioning
confidence: 94%
See 2 more Smart Citations
“…CBTI is considered first-line treatment for chronic insomnia and can be successfully utilized in patients with mTBI [100][101][102][103][104][105]. Previous reports have shown that CBTI reduced daytime fatigue and improved nocturnal sleep quality among patients with TBI [48].…”
Section: Insomnia and Circadian Dysregulationmentioning
confidence: 99%